Strengthening Nagari Regulatory Capacity through Participatory Legal Drafting–Based Legal Assistance in Kampuang Galapuang, Ulakan Tapakis Subdistrict - Bahktiar, Yusnanik; Gettari, Trie rahmi; Muchtar, Henni; Faisal, Muhammad; Ersya, Muhammad Prima; Rahmady, Windy (Jurnal Dedikasia : Jurnal Pengabdian Masyarakat, 2025)
This community service program aims to strengthen the regulatory capacity of the Nagari Government of Kampuang Galapuang, Ulakan Tapakis Subdistrict, Padang Pariaman Regency, through legal assistance in drafting the Nagari Regulation on Revenue Management. The initiative responds to challenges faced by the nagari, particularly the absence of clear regulations governing local revenue, which has hindered financial governance, program planning, and accountability mechanisms. The activity was carried out using a participatory empowerment approach involving socialization, training, Focus Group Discussions (FGD), and direct technical assistance in drafting the regulation. The results of the program show an improvement in participants’ understanding of basic regulatory concepts, principles of good governance, and legal drafting techniques. A collaboratively prepared draft of the Nagari Regulation on Revenue Management was produced as a tangible output. This program contributes to enhancing institutional capacity and supporting the realization of accountable, transparent, and legally grounded financial governance at the nagari level.